The effect of fluidzed bed drying temperature and packaging condition on retarding degradation of purple waxy rice during storage - Nittaya Junka; Chalermchai Wongs-Aree; Panida Boonyaritthongchai; Chaiwat Rattanamechaiskul (My University, 2017)
The objective of this research was to retard degradation in color, anthocyanin content, total phenolic content, antioxidant activity and free fatty acid content resulting in undesirable rancidity in purple waxy rice by applying post harvested drying technique and packaging.Paddy with initial moisture content of 25%w.b. was dried by a batch fluidized bed dryer with various temperatures of 100, 130 and 150ºC till the moisture reduced to 18.0%w.b.The dried paddy was then dehulled and packed, 50 g/bag, in a polypropylene woven bag, laminate bag and laminated bag within and without an oxygen absorber at ambient temperature for 90 days storage.After drying process, the results revealed that the proper temperature for drying paddy was at 130ºC which did not affect the postharvested quality of sample.However, the dried rice should be kept in the laminated bag containing an oxygen absorber for it was the most effective retarding rice quality degradation.
Keywords: Degradation; Food composition and properties